Antithrombotic therapy in peripheral arterial disease - Espinola-Klein, Christine; Weißer, Gerhard; Schmitt, Volker; Schwaderlapp, Melanie; Munzel, Thomas (Frontiers in Cardiovascular Medicine, 2022)
Background: Patients with peripheral arterial disease (PAD) are at increased risk for major adverse cardiovascular events (MACE) such as cardiovascular death, myocardial infarction, and stroke as well as major adverse limb events (MALE) such as amputation and acute limb ischemia. Therefore, prevention of thrombotic events is crucial to improve the prognosis of PAD patients. The current review article concludes current evidence and guideline recommendations about antithrombotic therapy in PAD patients. Antithrombotic therapy is highly effective to reduce MACE and MALE events in PAD patients. Recently, the concept of dual pathway inhibition (low-dose rivaroxaban plus acetylic salicylic acid (ASA)) has been tested in the COMPASS and VOYAGER-PAD trial. Compared to ASA alone dual pathway inhibition was superior to prevent MACE and MALE. After peripheral revascularization, in particular the risk for acute limb ischemia was reduced. In contrast, the risk for major bleeding is increased. Therefore, current guidelines recommend the combination of low-dose rivaroxaban and ASA in PAD patients with low bleeding risk. In patients with high bleeding risk, a single antiplatelet drug (preferable clopidogrel) is indicated. In patients with atherosclerotic vascular disease and indication for oral anticoagulation, no additional antiplatelet drug is necessary, as this would increase the risk of bleeding without improving the prognosis. Conclusion: Antithrombotic treatment reduces MACE and MALE and is recommended in all patients with PAD. Individual bleeding risk should always be considered based on the current data situation and an individual benefit-risk assessment must be carried out.